Melancholy and Suicide in the Work of Robert Burton - Potoček, Jan (Dějiny – teorie – kritika, 2021)
The aim of this study is to elucidate Burton’s conception of suicide. To understand it, it is first necessary to find out how Burton understood its main cause, melancholy. The first part of the study is therefore dedicated to an analysis of the concept of melancholy elaborated in his Anatomy of Melancholy. Conclusions drawn from this analysis are then used in the second part of this work to explain Burton’s notion of suicide and the treatment or prevention he suggests. In both parts, the main focus is on the Anatomy of Melancholy, which is used to explain both Burton’s position and intentions which motivated the writing of this treatise and his lifelong interest in the subject. The study is thus a contribution to research which views Burton’s thoughts and work within a historical, cultural, and conceptual context of Early Modern world but also to investigations of the impact of the work and Burton’s strategy regarding the effect the work should have on readers. Conclusions of this study point out the complexity and sophistication of Burton’s concept of suicide and show that it significantly diverges from the view commonly taken by contemporary judges, coroners, clergy, and physicians who also sometimes dealt with this issue. Keywords: Robert Burton, melancholy, suicide, sin, treatment, cultural and intellectual history.